Population genetics of Glossina fuscipes fuscipes from southern Chad - Ravel, Sophie; Mahamat, Mahamat Hissène; Ségard, Adeline; Argilés-Herrero, Rafael; Bouyer, Jérémy; Rayaisse, Jean-Baptiste; Solano, Philippe; Guihini Mollo, Brahim; Pèka, Mallaye; Darnas, Justin; Belem, Adrien Marie Gaston; Yoni, Wilfrid; et al. (Peer Community Journal)

(untitled)
In Subsaharan Africa, tsetse flies (genus Glossina) are vectors of trypanosomes causing Human African Trypanosomiasis (HAT) and Animal African Trypanosomosis (AAT). Some foci of HAT persist in Southern Chad, where a program of tsetse control was started against the local vector Glossina fuscipes fuscipes in the Mandoul focus in 2014, and in Maro in 2018. Flies were also sampled in 2018 in Timbéri and Dokoutou. We analyzed the population genetics of G. fuscipes fuscipes from the four tsetse-infested zones. The trapping samples were characterized by a strong female biased sex-ratio, except in Timbéri and Dokoutou that had high tsetse densities. Apparent density and effective population density appeared smaller in the main foci of Mandoul and Maro and the average dispersal distance (within the spatial scale of each zone) was as large as or larger than the total length of each respective zone. The genetic signature of a population bottleneck was found in the Mandoul and Timbéri area, suggesting a large ancient interconnected metapopulation that underwent genetic subdivision into small, isolated pockets due to adverse environmental conditions. The long-range dispersal and the existence of genetic outliers suggest a possibility of migration from remote sites such as the Central African Republic in the south (although the fly situation remains unknown there) and/or a genetic signature of recent exchanges. Due to likely isolation, an eradication strategy may be considered for sustainable HAT control in Mandoul focus. Another strategy will probably be required in Maro focus, which probably experiences much more exchanges with its neighbors.